PELATIHAN PROGRAM SIARAN RADIO SEBAGAI MEDIA ALTERNATIF DI LINGKUNGAN SANTRI - Syaifudin, Ahmad Anif; Muizzah, Awendsa Urfatunnisa Tasyaul (Universitas Budi Luhur, 2025)
Radio is an important mass media for the public seeking information, entertainment, and education, and Uniss FM Radio with the tagline